Women and Lockean Theory: John Locke, Rachel Speght, and Egalitarian Personhood - Gillespie, Katharine; van der Vossen, Bas (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2024)
Liberal political thought affirms the moral equality of all persons. The Lockean tradition within liberalism captures this equality by endowing people with equal natural rights. However, a powerful line of criticism holds that the theory fails to live up to its egalitarian billing by treating men and women differently. This article offers a rational reconstruction of the Lockean position on gender equality, and the rights of women in particular. We propose a novel interpretative method which puts Locke into conversation with a contemporary female author, Rachel Speght. In Speght, we find an interesting argument supporting an egalitarian Lockean view, grounded in familiar Lockean assumptions, using familiar Lockean arguments. Voices like Speght have long been unjustly neglected in the liberal tradition. By constructing this imagined conversation, we offer a stronger foundation for Lockean liberalism, and begin to incorporate excluded voices in the formulation of that tradition.